2001
DOI: 10.1136/bjsm.35.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Mountain biking injuries in rural England

Abstract: Background-OV road mountain biking is now an extremely popular recreation and a potent cause of serious injury. Aim-To establish the morbidity associated with this sport. Methods-Data were collected prospectively over one year on all patients presenting with an injury caused by either recreational or competitive oV road mountain biking. Results-Eighty four patients were identified, 70 males and 14 females, with a mean age of 22.5 years (range 8-71). Most accidents occurred during the summer months, most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 4 publications
6
60
1
4
Order By: Relevance
“…In road cycle racing, overuse injuries are reported of the median nerve in the carpal tunnel [2], this is observed in off-road motorcyclists as well [3] the ulnar nerve in Guillon's Canal [2] the perineal nerve, the cervical [4] and lumbar spine and in the knees. Although recent studies have reported injuries in recreational and competitive off-road biking [5][6][7][8][9][10] little is known about overuse injuries in competitions [4,[8][9][10]. In 2002 it was recommended [11] that further investigations in mountain biking should address overuse injuries.…”
Section: Introductionmentioning
confidence: 99%
“…In road cycle racing, overuse injuries are reported of the median nerve in the carpal tunnel [2], this is observed in off-road motorcyclists as well [3] the ulnar nerve in Guillon's Canal [2] the perineal nerve, the cervical [4] and lumbar spine and in the knees. Although recent studies have reported injuries in recreational and competitive off-road biking [5][6][7][8][9][10] little is known about overuse injuries in competitions [4,[8][9][10]. In 2002 it was recommended [11] that further investigations in mountain biking should address overuse injuries.…”
Section: Introductionmentioning
confidence: 99%
“…RESEARCH epidemiology of less severely injured cyclists, 9,10,[12][13][14][15][16][17]19 this retrospective cohort study analyzed only patients with severe multisystem injuries (ISS ≥ 12). This was affirmed by an overall median ISS of 17, ICU admission rate of 26.4%, surgical intervention rate of 33.3% and mortality of 6.6%.…”
Section: E35mentioning
confidence: 99%
“…4 Conversely, mountain biking injuries accounted for only 1.6% of all severe trauma patient admissions in this area from 1992 to 2002 (about 1-6 injuries per 100 000 patients per year). 5 Although observational studies of bicycling injuries are common, [3][4][5][6][7][9][10][11][12][13][14][15][16][17] to our knowledge, our study is the first to compare the overall major trauma epidemiology of street and mountain bicycling in detail. Few reports have discussed experience with severe bicycling-related multisystem injuries that require emergent surgical intervention or intensive care unit (ICU) admission.…”
mentioning
confidence: 99%
“…However, little is known about the rik of injury involved in participation. Severe injuries including dislocation and fracture of the cervical spine and a case of incomplete tetraplegia was reported by Jeys et al [5] andApsingi et al [6].…”
Section: Chicken Loopmentioning
confidence: 99%
“…However, in McDermott's study of 1710 bicycling injuries, helmet use has reduced the risk of head injuries by 39% and the risk of facial injury by 28% [10]. The importance of head protection has been appreciated with the majority of off mountain bike cyclists wearing helmets [5]. According to Carmont, most serious injuries to the head and neck occur whilst falling over the handlebars rather than falling off the bike to the side, which tends to result in the lower limbs injuries.…”
Section: Chicken Loopmentioning
confidence: 99%